2015
DOI: 10.15406/jlprr.2015.02.00026
|View full text |Cite
|
Sign up to set email alerts
|

Spirometric Values in Sitting, Standing and Supine Position

Abstract: IntroductionSpirometry is a physiological test that measures how an individual inhales or exhales volumes of air as a function of time. The primary signal measured in spirometry may be volume or flow. Spirometry is invaluable as a screening test of general respiratory health. It is commonly used to distinguish between restrictive and obstructive lung diseases, identifying patients susceptible to pulmonary barotraumas and bronchial hyper responsivity. It is also used in assessing pre-operative anesthetic risk i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…In this study, on the first day of admission elderly patients with healthy lungs showed significantly lower FVC (2.14 ± 0.54 L) and FVC% (71.66% ± 12.53%) than the normal range specified in the guideline of the American Thoracic Society and the values of Cebria et al’s [10] study on sedentary frail older women (77.7~83.0%). It has been well proven that lower position reduces spirometric values [11, 12]. The low FVC of patients with healthy lungs and hip fracture in the present study may be attributed to postural limitations, physical pain, and stress weakness.…”
Section: Discussionsupporting
confidence: 53%
“…In this study, on the first day of admission elderly patients with healthy lungs showed significantly lower FVC (2.14 ± 0.54 L) and FVC% (71.66% ± 12.53%) than the normal range specified in the guideline of the American Thoracic Society and the values of Cebria et al’s [10] study on sedentary frail older women (77.7~83.0%). It has been well proven that lower position reduces spirometric values [11, 12]. The low FVC of patients with healthy lungs and hip fracture in the present study may be attributed to postural limitations, physical pain, and stress weakness.…”
Section: Discussionsupporting
confidence: 53%